Analizing the Emerging Inmersión of ARGS through the Transimmersion Concept - Ruiz García, David; Meléndez González Haba, Guadalupe (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The immersive element in alternative reality games (ARGs) is considered a fundamental ingredient of the genre, something problematic in view of the confusion between fiction and reality that characterises it. This paper aims to analyse the immersive regime of ARGs, conceptualising its peculiarities through a new term, transimmersion. The conditions necessary to consider immersion and its particular adaptation to ARG forms give rise to a unique context. The hypotheses that posited an immersive nature of ARGs mutant in their manifestations and variable in their levels, are corroborated by showing a new conceptual scenario.